Vitamin D for the Treatment of Epilepsy: Basic Mechanisms, Animal Models and Clinical Trials - Pendo, Kevin; DeGiorgio, MD, Christopher M. (Frontiers in Neurology, 2016)
There is increasing evidence supporting dietary and alternative therapies for epilepsy, including the ketogenic diet, modified Atkins diet, and omega-3 fatty acids. Vitamin D is actively under investigation as a potential intervention for epilepsy. Vitamin D is fat soluble steroid which shows promise in animal models of epilepsy. Basic research has shed light on the possible mechanisms by which Vitamin D may reduce seizures, and animal data support the efficacy of Vitamin D in rat and mouse models of epilepsy. Very little clinical data exists to support the treatment of human epilepsy with Vitamin D, but positive findings from preliminary clinical trials warrant larger Phase I and II clinical trials in order to more rigorously determine the potential therapeutic value of Vitamin D as a treatment for human epilepsy.